PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Konsumen Starbucks Veteran Raya Bintaro di Jakarta Selatan) - Yuliana Sari; Ravindra Safitra Hidayat (CV. Denasya Smart Publisher, 2024)
The objective of this study was to examine the impact of Price Perception, Service Quality, and Promotion on the purchasing decisions of Starbucks. Primary data from the distribution of questionnaires was used as the data source in this study. Clients of the Starbucks in Veteran Raya Bintaro, South Jakarta, make up the study's demographic. With a sample size of 96 respondents, this study used a survey method that made use of non-probability techniques like purposive sampling. The utilised analytical tool is SPSS version 26. Research can proceed because all investigated variables are reliable and valid, and they have all been shown to be feasible by the classical assumption test. According to the study's findings, customers at Starbucks Veteran Raya Bintaro in South Jakarta are significantly influenced by price perception, service quality, and promotions while making decisions about what to buy.